Reduced genetic diversity and low effective size in peripheral northern European catfish Silurus glanis populations. Issue 6 (6th November 2019) - Palm, Stefan; Vinterstare, Jerker; Nathanson, Jan Eric; Triantafyllidis, Alexandros; Petersson, Erik
Abstract: Using 10 polymorphic microsatellites and 1251 individual samples (some dating back to the early 1980s), genetic structure and effective population size in all native and introduced Swedish populations of the European wels catfish or Silurus glanis were studied. Levels of genetic variability and phylogeographic relationships were compared with data from a previous study of populations in other parts of Europe. The genetically distinct Swedish populations displayed comparably low levels of genetic variability and according to one‐sample estimates based on linkage disequilibrium and sib ship‐reconstruction, current local effective population sizes were lower than minimum levels recommended for short‐term genetic conservation. In line with a previous suggestion of postglacial colonisation from a single refugium, all Swedish populations were assembled on a common branch in a star‐shaped dendrogram together with other European populations. Two distinct subpopulations were detected in upper and lower habitats of River Emån, indicating that even minor dispersal barriers may restrict gene flow for wels in running waters. Genetic assignment of specimens encountered in the brackish Baltic Sea and in lakes where the species does not occur naturally indicated presence of long‐distance sea dispersal and confirmed unauthorised translocations, respectively.